Efektifitas Model Pembelajaran Berbasis Masalah Pada Materi Asam Basa Terhadap Hasil Belajar Siswa Kelas XI di SMA Negeri 1 Maligano - Satna, Satna Rahayu; Maysara , Maysara; Haetami , Aceng (Chemistry Education Practice, 2025)
This study aims to determine the chemistry learning outcomes of students after being taught using the Problem-Based Learning (PBL) model on acid–base material; to examine the effectiveness of the PBL model in improving students’ learning outcomes on acid–base topics; and to identify students’ responses toward the use of the PBL model in learning acid–base concepts. This research employed a pre-experimental design with a one-group pretest–posttest. The study subjects were 31 students of class XI A¹ at SMA Negeri 1 Maligano in the 2024/2025 academic year. Data were collected through learning outcome tests and student response questionnaires. The findings indicate that students taught using the PBL model achieved an average chemistry learning outcome score of 86.6, which falls into the “excellent” category. The PBL model was found to be effective in improving students’ chemistry learning outcomes in acid–base material, as reflected in an N-gain score of 0.78, which is categorized as high. In addition, students showed positive responses toward the implementation of the PBL model, reaching 74.78% which is categorized as good.